Optimal incentive contracts under inequity aversion - Florian Englmaier; Achim Wambach (Institute for the Study of Labor (IZA), 2005)
We analyze the Moral Hazard problem, assuming that agents are inequity averse. Our results differ from conventional contract theory and are more in line with empirical findings than standard results. We find: First, inequity aversion alters the structure of optimal contracts. Second, there is a strong tendency towards linear sharing rules. Third, it delivers a simple rationale for team based incentives in many environments. Fourth, the Sufficient Statistics Result is violated. Dependent on the environment, optimal contracts may be either overdetermined or incomplete.
Keywords: D23; D63; J31; J33; M12; Z13; 330; contract theory; linear contracts; incentives; sufficient statistics result; inequity aversion; incomplete contracts